The Effect of Environmental Costs and Profitability on Environmental Performance - Hermawan, Dedi; Susilo, Bambang Widjanarko; Khaq, Zahra Dinul; Ratnaningrum, Ratnaningrum (Journal of Management and Informatics, 2025)
This research aims to analyze the influence of environmental costs and profitability on ecological performance at companies in Indonesia. This study is motivated by the phenomenon where many companies allocate ecological costs, but their effectiveness in improving environmental performance is still questionable. By using the method Weighted Least Squares (WLS) to overcome heteroscedasticity, this research tests the relationship between these variables using secondary data from company financial reports. The research results show that Environmental Cost does not have a significant effect on Environmental Performance, indicating that environmental spending is often used as a legitimation tool rather than as a real sustainability strategy. ROE has a significant negative effect on Environmental Performance, which shows that companies with high profitability focus more on achieving profits than on environmental investments. On the contrary, Firm Size has a significant positive effect on Environmental Performance, asserting that large companies are better able to implement environmental policies because they have more resources and face greater stakeholder pressure. This research provides implications for regulators to increase transparency in environmental spending as well as for investors in considering sustainability aspects in their investment decisions.